Designing cyber safety and security literacy programs to enhance cyber security competency of prospective teachers - Thangan, Santhosh; Kaliappan, Thiyagu; Vijayan, Vrinda; Abhinav, Venukanti Sai; Shanthipalla, Ashalatha (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the design, development, and evaluation of a cyber safety and security literacy program (CSLP) aimed at enhancing cyber security competency (CSC) among prospective teachers. Utilizing a research and development (R&D) method, the program was structured using the analysis, design, development, implementation, evaluation (ADDIE) model to create instructional modules covering key cyber safety topics. The validity of the program was ensured through expert evaluations, and its effectiveness was tested via a pre-experimental research design with a single group of 50 prospective teachers from training colleges in Kerala, India. Pre- and post-test assessments were conducted using a standardized CSC scale. Statistical analysis, including t-tests and Cohen’s d, revealed a significant improvement in participants’ CSC, with a large effect size (Cohen’s d=4.32), indicating the program’s substantial impact. This study emphasizes the importance of incorporating structured cyber safety education into teacher training programs to bridge the gap between digital engagement and online safety. The findings also highlight the broader need for integrating cyber security literacy in professional contexts to foster responsible digital behavior.